2010
DOI: 10.1186/1471-2466-10-30
|View full text |Cite
|
Sign up to set email alerts
|

β2-agonists promote host defense against bacterial infection in primary human bronchial epithelial cells

Abstract: BackgroundAirway epithelial cells are critical in host defense against bacteria including Mycoplasma pneumoniae (Mp) in chronic obstructive pulmonary disease (COPD) and asthma. β2-agonists are mainstay of COPD and asthma therapy, but whether β2-agonists directly affect airway epithelial host defense functions is unclear.MethodsEpithelial cells from bronchial brushings of normal (n = 8), asthma (n = 8) and COPD (n = 8) subjects were grown in air-liquid interface cultures, and treated with cigarette smoke extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 40 publications
4
22
0
Order By: Relevance
“…Using Mp as an infection model, NCI-H292 cells treated with IL-13 demonstrated higher Mp levels than those without IL-13 treatment (Figure 3), which is similar to the results in our previous publications in primary human bronchial epithelial cells (16,17). Therefore, the NCI-H292 cell line was used as a valuable model to study the mechanisms (e.g., Sp1) underlying IL-13-induced MUC18 expression.…”
Section: Mechanisms Of Il-13-induced Muc18 Expression In Epithelial Csupporting
confidence: 74%
See 3 more Smart Citations
“…Using Mp as an infection model, NCI-H292 cells treated with IL-13 demonstrated higher Mp levels than those without IL-13 treatment (Figure 3), which is similar to the results in our previous publications in primary human bronchial epithelial cells (16,17). Therefore, the NCI-H292 cell line was used as a valuable model to study the mechanisms (e.g., Sp1) underlying IL-13-induced MUC18 expression.…”
Section: Mechanisms Of Il-13-induced Muc18 Expression In Epithelial Csupporting
confidence: 74%
“…Brushed bronchial epithelial cells were cultured under ALI conditions with or without IL-13 (10 ng/ml) treatments as previously reported (17,(19)(20)(21)(22) (see details in the online supplement). After 16 days of treatment, cells were harvested into TRIzol (Invitrogen, Carlsbad, CA) and Western lysis buffer for MUC18 mRNA and protein detection, respectively.…”
Section: Brushed Bronchial Epithelial Cell Ali Culturesmentioning
confidence: 99%
See 2 more Smart Citations
“…This likely reflects increased surface tension and decreased ASL water content caused by loss of surfactant and ion transport properties in BPIFA1-deficient animals (51, 57). Gross and colleagues suggested that the induction of BPIFA1 expression in airway epithelial cells by b 2 -agonist treatment should improve Mp clearance through the mechanisms described above (60). BPIFA1 may also modulate the secretion of other antimicrobial proteins in the airway because naive BPIFA1-deficient mice exhibited decreased expression of antimicrobial peptides LL37, lactoferrin, and lyzozyme.…”
Section: Biological Properties Of Bpifa1 Antimicrobialmentioning
confidence: 99%